Pembuatan Mesin Pencacah Biji Jagung dengan Motor Listrik sebagai Penggerak - Nofriadi, Nofriadi; Widodo, Tri Wahyu; Fadhlulrahman, Zaki; Rosa, Yazmendra; Yetri, Yuli (JURNAL INTEGRASI, 2024)
Processing corn kernels into fine corn or corn flour has been widely used various methods to obtain good results and maximum results, therefore a machine was created corn grain chopper with an electric motor so that it can be used by small-scale farmers or MSMEs. The purpose of making this tool is to make corn kernel chopper components such as knife blades, home chopper, hooper, and sieve, as well as knowing the results of the process of chopping corn kernels, and know the quality of the results of the corn kernel chopper. The stages of making this machine are: manufacturing components, component assembly and tool testing. The specifications of the corn grain chopper machine are length 890 mm, width 420 mm, height 1090 mm. The driving source for this corn seed chopper machine is the motor Â¼ HP electric with 1400 rpm rotation, using a shaft made of ST 37 steel, in bearings Use a size of 1 inch. The transmission system uses a shaft connected to an electric motor and is connected directly to the blade. After the trial was carried out 3 times, the results were not different from the level of fineness, the enumeration results were very satisfactory and the capacity was obtained machine is 40 kg/hour. The result of after 3 tests, the results did not differ much from the level of refinement for each test. This machine is suitable for owners of large farms, because it is easy to carry.